AppréciAtion de l’Activité protéolytique d’une enzyMe coAgulAnte extrAite des fleurs de chardon - BENABDERRAHMENE, Abid (My University, 2025)
The preparation of cheese curds by milk coagulation using thistle flower extracts is an original technology specific to certain Algerian regions. The aim of our study is to characterize the coagulating power of the enzymatic extract of this plant, in order to make up for the lack of scientific data on this coagulant. This characterization will make it possible to propose technological solutions to replace the commercial coagulating enzyme used by cheese dairies. In fact, preliminary tests carried out on the plant's flower indicate an interesting coagulant activity for use in the manufacture of mixed cheese curds. The enzymatic extract obtained from thistle flowers showed good coagulation of a cheese milk obtained from a “low heat” cheese milk powder. The technological times (setting times) obtained, 1820 seconds for the thistle flower enzyme and 1500 seconds for the commercial enzyme, are in line with the IDF standard set between 960 seconds and 1920 seconds to obtain a compliant enzymatic cheese curd. This enzymatic extract from thistle flowers gave the expected results for the manufacture of a mixed curd cheese. These results enable us to envisage a scientific approach to the industrial application of natural coagulants for the substitution of commercial coagulants in the manufacture of local cheeses and the preservation of their typicality.
Keywords: Enzyme extract; thistle flowers; technological times; mixed cheese curds